2021
DOI: 10.1111/jocn.15651
|View full text |Cite
|
Sign up to set email alerts
|

Learning to be a doctoral supervisor: Experiences and views of nurse supervisors of higher degree research students

Abstract: Aims and objectives Given the importance of doctoral training to the future of the discipline, we sought to gain insight into nurse doctoral supervisor's experiences of supervision training and preparation and their views on what quality training for doctoral supervisors in nursing would look like. Background Doctorally prepared nurses have been found to contribute significantly to improvements in knowledge to inform patient care; yet there is little focus on the development of this aspect of the nursing workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Institutions should have in place, and enforce, a policy regarding the maximum number of doctoral students which a supervisor can accept for supervision to ensure that each individual doctoral student receives sufficient time and attention [15,24]. Supervision takes a significant amount of time and there needs to be a realistic workload recognition of this by the institution, so that adequate time across the academic year can be provided [15,25]. This time requirement must also be understood by the supervisor before they make a commitment to supervise a new doctoral student.…”
Section: Selecting the Right Doctoral Studentmentioning
confidence: 99%
See 2 more Smart Citations
“…Institutions should have in place, and enforce, a policy regarding the maximum number of doctoral students which a supervisor can accept for supervision to ensure that each individual doctoral student receives sufficient time and attention [15,24]. Supervision takes a significant amount of time and there needs to be a realistic workload recognition of this by the institution, so that adequate time across the academic year can be provided [15,25]. This time requirement must also be understood by the supervisor before they make a commitment to supervise a new doctoral student.…”
Section: Selecting the Right Doctoral Studentmentioning
confidence: 99%
“…Doctoral supervision is a collaborative process which means that the relationship between the supervisor and the doctoral student is of key significance [25]. In fact, the timely completion of a doctoral student is often dependent upon the quality of the relationship which they have with their supervisor [32].…”
Section: Considering the Supervisor-doctoral Student Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has identified that there is often insufficient training of supervisors to help students complete this [126]. Even where training is provided by institutions, this has proven to be inadequate [127] due to its focus on the administration of the degree rather than subject content or pedagogy [128]. These problems are exacerbated when the institutional training is compulsory, with the consequence of lack of engagement from those doctoral supervisors forced into attendance-ultimately the staff remain unconvinced of the efficacy of such resources [129].…”
Section: How To Train Supervisors To Support Doctoral Students To Pub...mentioning
confidence: 99%
“…This is evidenced by the fact that three Australian nursing schools were in the top 20 of the World QS rankings in 2021. Issues of diversity, equity and inclusion are seen as critical ( Jackson et al., 2021 ). Nursing continues to perform exceptionally well in the interdisciplinary Evaluation of Research in Australia, which emphasises the quality of research publications and research impact.…”
Section: International Perspective On Nursing Researchmentioning
confidence: 99%